Cariogenic effects related to childhood nutrition (Research, Society and Development, 2025)
Dental caries is a highly prevalent multifactorial disease among children, influenced by factors such as a diet rich in fermentable sugars, eating frequency, and oral hygiene habits. In childhood, these factors are even more critical, as eating habits are still developing and the consumption of processed foods is frequent. This study aims to analyze, through a literature review, the cariogenic effects of childhood diet, seeking to understand the influence of foods and their frequency of consumption on the incidence of dental caries. The research will be conducted in the Scopus and MEDLINE (via PubMed) databases, using the descriptors "dental caries," "cariogenic diet," and "children”. The results were analyzed and showed that foods and beverages high in sugar, such as sweets, juices, and soft drinks, are strongly associated with an increased prevalence and severity of tooth decay. It was also observed that the early introduction of these foods, even in the first year of life, increases the risk of severe early tooth decay, while regular consumption of healthy foods demonstrated a protective effect against the disease.